Aplikasi Jaringan Syaraf Tiruan untuk Pendugaan Mutu Mangga Segar Secara Non-Destruktif - Sandra, Sandra (Jurnal Teknologi Pertanian, 2005)
The objective of this study was to estimate grade of mango with artificial neural network.  There are three grade of mango: grade I, grade II and grade III. Each grade consists of 40 samples. The Artificial Neural Network consists of three model; first model: 3 input, second model: 5 input and third model: 7 input.  Each of models consists of three outputs with 1000, 2500, and 5000 iteration, and 3, 5, and 7 hidden layers. The result of this study show that the accuracy of artificial neural network in grade of mango: (1) the first model 60% - 100%;  (2) the second model 90% and (3) the third model 90 %. The conclusion of this study is the artificial neural network can predict the grade of mango and the best model is the third model.   Keywords: Mango, grade, artificial neural network